A new entropy-based metallic material stress relaxation engineering prediction method. (May 2022) - Lian, YeDa; Wang, Xiaoshuai; Wang, Jundong; Wen, Zhixun
Highlights: Based on entropy theory and damage model, a new stress relaxation prediction model is proposed in this paper. At present, there are few studies on stress relaxation of DD6 material. The stress relaxation of DD6 material is studied in this paper. The prediction model has been verified by stress relaxation tests for a variety of materials, and shows wide applicability. Abstract: The stress relaxation behavior of metallic materials has great influence on its mechanical properties under service conditions especially with high temperatures. This paper proposed a new engineering type of stress relaxation prediction model based on continuous damage mechanics and the second law of thermodynamics. Stress relaxation experiments of nickel-based single crystal DD6 were carried out at different temperatures. The proposed model was verified by experimental data of DD6 and other metallic materials, the results show that the model has good prediction accuracy.